Protecting Rights and Building Capacities: Challenges to Global Mental Health Policy in Light of the Convention on the Rights of Persons with Disabilities. Issue 1 (12th April 2013) - Wildeman, Sheila
<x xml:space="preserve">Abstract</x> The World Health Organization (WHO) has identified mental health as a priority for global health promotion and international development to be targeted through promulgation of evidence‐based medical practices, health systems reform, and respect for human rights. Yet these overlapping strategies are marked by tensions as the historical primacy of expert‐led initiatives is increasingly subject to challenge by new social movements — in particular, disabled persons' organizations (DPOs). These tensions come into focus upon situating the WHO's mental health policy initiatives in light of certain controversies arising under the Convention on the Rights of Persons with Disabilities (CRPD), particularly as it applies to persons with mental (psychosocial) disabilities. I examine two such controversies — concerning, respectively, the legitimacy of involuntary psychiatric interventions and the legitimacy of regimes of substitute decision‐making. These controversies illustrate the radical challenges to global and domestic mental health policy that have gained new momentum through the participation of DPOs in the CRPD process. At the same time, they illustrate the need for ongoing, inclusive forums for deliberation at the nexus of mental health policy and human rights, aimed at enabling human flourishing within a framework of respect for diversity.